The Antiangiogenic Activity of Polyphenol-Rich Extracts and Its Implication on Cancer Chemoprevention. Issue 1 (2nd January 2020) - Chojnacka, Katarzyna; Lewandowska, Urszula
ABSTRACT: Plant-based diet has many valuable properties, and natural polyphenols that are contained in fruits, vegetables or beverages have numerous beneficial functions. They are well-known for supporting health, having anti-inflammatory, antioxidant, pro-apoptotic and anti-cancer (including anti-angiogenic) activities. Polyphenol-rich extracts have also the ability to prevent the development of angiogenesis, modulating some of factors and cellular mechanisms associated with this process. They also have an impact on the reduction of vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1 (HIF-1) and angiopoietins. Additionally, they can modulate multiple signaling pathways, such as PI3K or ERK1/2. What is more, they have the ability to inhibit or regress formation of blood vessel networks in tumors, attenuate migration and invasion of cancer cells, as well as reduce tumor growth. This review provides a current stage of knowledge, concentrating on polyphenol-rich extracts and their anti-angiogenic properties. Most of the in vitro and in vivo studies suggest that natural polyphenols may be another therapeutic agent in anti-angiogenic therapies.